The Relationship of Motor Ability to the Level of Physical Fitness of State Elementary School Students 3 Years Aged 10-12 Years - Bimantoro Unggul Anggoro; Moch Fahmi Abdulaziz (Universitas Negeri Semarang, 2026)
Physical fitness among elementary school students is an important factor in supporting optimal growth, learning participation, and the development of healthy lifestyles from an early age. At the elementary school level, motor skills such as speed, agility, strength, balance, and endurance are essential components that influence students’ physical activity performance and overall fitness condition. This study aims to analyze the relationship between motor skills and physical fitness levels among students of State Elementary School 3 Wonosari aged 10–12 years. This research employed a quantitative approach with a correlational design to determine the direction and strength of the relationship between variables without providing any specific treatment. The research population consisted of all fourth-grade students totaling 55 students, and the sampling technique used was total sampling. Motor skills were measured through a 30-meter sprint test (speed), Illinois Agility Test (agility), Vertical Jump (leg muscle strength/power), Stork Stand (balance), and a 1000-meter run (endurance). The level of physical fitness was measured using the Indonesian Physical Fitness Test (TKJI) instrument according to the norms for ages 10–12 years. Before hypothesis testing, the data were analyzed through prerequisite tests, namely the normality test and linearity test, to ensure that the assumptions of parametric analysis were met. The analysis of the relationship between variables was conducted using the Pearson Product-Moment correlation test with a significance level of α = 0.05. The results of the analysis indicated a positive and significant relationship between motor skills and students’ physical fitness levels, with the strength of the relationship categorized as moderate to strong. Based on these findings, it can be concluded that the better the students’ motor skills, the higher their level of physical fitness. The implications of this study emphasize the importance of developing basic motor components in physical education learning at the elementary school level as a systematic effort to improve students’ physical fitness optimally and sustainably.